"Characterization of ELEKTA SRS cone collimator using high spatial resolution monolithic silicon detector array". (22nd May 2018) - Shukaili, Khalsa Al; Corde, Stéphanie; Petasecca, Marco; Pereveratylo, Vladimir; Lerch, Michael; Jackson, Michael; Rosenfeld, Anatoly
Abstract: Purpose: To investigate the accuracy of the dosimetry of radiation fields produced by small ELEKTA cone collimators used for stereotactic radiosurgery treatments (SRS) using commercially available detectors EBT3 Gafchromic TM film, IBA Stereotactic diode (SFD), and the recently developed detector DUO, which is a monolithic silicon orthogonal linear diode array detector. Methods: These three detectors were used for the measurement of beam profiles, output factors, and percentage depth dose for SRS cone collimators with cone sizes ranging from 5 to 50 mm diameter. The measurements were performed at 10 cm depth and 90 cm SSD. Results: The SRS cone beam profiles measured with DUO, EBT3 film, and IBA SFD agreed well, results being in agreement within ±0.5 mm in the FWHM, and ±0.7 mm in the penumbra region. The output factor measured by DUO with 0.5 mm air gap above agrees within ±1% with EBT3. The OF measured by IBA SFD (corrected for the over‐response) agreed with both EBT3 and DUO within ±2%. All three detectors agree within ±2% for PDD measurements for all SRS cones. Conclusions: The characteristics of the ELEKTA SRS cone collimator have been evaluated by using a monolithic silicon high spatial resolution detector DUO, EBT3, and IBA SFD diode. The DUO detector is suitable for fast real‐time quality assurance dosimetry in small radiation fields typical for SRS/SRT. This has been demonstrated by its good agreement of measured doses with EBT 3 films.